P2H Modeling and Operation in the Microgrid Under Coupled Electricity–Hydrogen Markets - Liu, Hongxin; Wang, Yueyao; Xu, Feifei; Wu, Mengkai; Jiang, Kai; Yan, Xiaohe; Liu, Nian (Frontiers in Energy Research, 2021)
The uncertainty and volatility of wind power have led to large-scale wind curtailment during grid connections. The adoption of power-to-hydrogen (P2H) in a microgrid (MG) can mitigate the renewable curtailment by hydrogen conversion and storage. However, the multi-energy trading in a hydrogen-coupled electricity market makes the corresponding operation and trading strategies more complex. In this paper, a bi-level equilibrium model is proposed to minimize the energy cost of microgrids with multi-type P2H in coupled electricity-hydrogen markets. Firstly, a microgrid operation model applied to different P2H systems including alkaline electrolysis cell (AEC), proton exchange membrane electrolysis cell (PEMEC) or solid oxide electrolysis cell (SOEC) is proposed at the upper level. Secondly, an electricity market-clearing model and a hydrogen market model are constructed at the lower level. Then, the diagonalization algorithm is adopted to solve the multi-market equilibrium problem. Finally, case studies based on an IEEE 14-bus system are conducted to validate the proposed model, and the results show that the microgrid with P2H could gain more profits and helps to increase the renewable penetration.